Incipient plasticity and surface damage in LiTaO3 and LiNbO3 single crystals. (5th September 2018) - Gruber, M.; Leitner, A.; Kiener, D.; Supancic, P.; Bermejo, R.
Abstract: The outstanding functional properties of single crystals used in many engineering applications often rely on their surface quality. The associated grinding process in single crystals is known to introduce surface or sub-surface defects (cracks), which may compromise the functionality and/or structural integrity of the final device. The small size of such defects often yields relatively high strength values, but also usually large scatter which implies low reliability. The aim of this work is to analyze the onset of surface contact damage in single crystals with respect to crystal orientation and elastic properties. LiTaO3 and LiNbO3 anisotropic single crystal samples are investigated using nanoindentation techniques and focused ion beam based sub-surface analyses. Experimental findings show that the onset of damage is correlated to weaker cleavage planes. At this stage also traces of plastic deformation on the contact surface due to twinning are observed. Further load increase revealed contact cracks in both materials; their morphology and extension being related to the orientation of the cleavage planes and elastic properties of the crystals. Our results advance the understanding of damage in anisotropic materials such as LiTaO3 and LiNbO3, and can generally be utilized to assess the onset of damage in other brittle materials. Graphical abstract: Unlabelled Image